(untitled) (Pubmet, 2022)
The TRIPLE project (Targeting Researchers through Innovative Practices and Linked Exploration) is developing a discovery platform dedicated to the social sciences and humanities (SSH). It gathers 21 partners from 15 European countries and is funded under the European Commission programme INFRA EOSC-02-2019 “Prototyping new innovative services’’. The multicultural and multilingual GoTriple platform is harvesting three kinds of data available in nine languages (Croatian, English, French, German, Italian, Greek, Polish, Portuguese, and Spanish). The beta version, available from October 2021, gives access to more than 1.6 million publications and data sets from big aggregators and smaller repositories to cover all SSH disciplines. GoTriple also responds to requests from SSH researchers to foster interdisciplinarity and enhance collaboration. For this reason, GoTriple will make available researcher profiles and research projects. Five innovative services complement this approach by making available the so called Trust Building System, Recommender System, Visualization Tool, Open Annotation Tool, and Crowdfunding Platform. The TRIPLE project seeks to improve fairness of open science and ensure that research material is more accessible to SSH researchers and to society by (1) making SSH scientific publications available to as many people as possible without popularizing or simplifying the content and by (2) encouraging better connections between SSH and various sections of society (e.g. SMEs, Journalists, Policy Makers). The TRIPLE project has made use of a co-design approach from the very start (late 2019), which includes relevant stakeholders through interviews and workshops to ensure that their needs are understood and that the platform will meet their needs. The TRIPLE project has also developed an innovative approach to evaluate the success of the platform based on compass indicators of equality, diversity, and community building. These indicators will help to advance open science. Moreover, the project is currently engaging users to build a thriving community. The OPERAS research infrastructure, supporting open scholarly communication in the social sciences and humanities in the European Research Area will take an active part in the governance and sustainability of the platform. At the conference we will present: ▸ some aspects of the research underpinning the creation of GoTriple, including the Co-design work, ▸ the key functionalities of GoTriple and how they can benefit research in the humanities, ▸ how the platform will ensure discoverability and accessibility of SSH resources and highlight European diversity in terms of culture, language, and practices, and ▸ the complexities of building new technologies serving the humanities.